2018
DOI: 10.1101/468264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissociation of fear initiation and maintenance by breathing-driven prefrontal oscillations

Abstract: Does the body play an active role in emotions? Since the original James/Cannon controversy this debate has mainly been fueled by introspective accounts of human experience. Here, we use the animal model to demonstrate a physiological mechanism for bodily feedback and its causal role in the stabilization of emotional states. We report that during fear-related freezing mice breathe at 4Hz and show, using probabilistic modelling, that optogenetic perturbation of this feedback specifically reduces freezing mainten… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(19 reference statements)
2
9
0
Order By: Relevance
“…Our results indicating a role for 4 Hz BLA-mPFC oscillations in stabilizing freezing bouts adds to recent reports of a respiration-synchronized 4 Hz mPFC oscillation that can similarly stabilize freezing behavior [53][54][55][56] . Based on these multiple lines of studies, we may attempt to build a general framework wherein 4 Hz respiration-synchronized oscillations can entrain limbic circuits in both an experience-independent and experiencedependent manner.…”
Section: Discussionsupporting
confidence: 85%
“…Our results indicating a role for 4 Hz BLA-mPFC oscillations in stabilizing freezing bouts adds to recent reports of a respiration-synchronized 4 Hz mPFC oscillation that can similarly stabilize freezing behavior [53][54][55][56] . Based on these multiple lines of studies, we may attempt to build a general framework wherein 4 Hz respiration-synchronized oscillations can entrain limbic circuits in both an experience-independent and experiencedependent manner.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, it was not possible to analyze the temporal pattern of activity in the 3-5 Hz delta band due to edge effects due to shock artefact. However, others have found that a 4Hz oscillation develops in the mPFC during freezing behavior and that this oscillation was driven by respiration (Moberly et al, 2016;Karalis et al, 2016;Bagur and Benchenane, 2018). In line with these studies, we recently showed that respiratory frequency and delta activity frequency were highly correlated during freezing (Dupin et al, 2019).…”
Section: Does Respiratory Rhythm Modulate the Temporal Patterns Obsersupporting
confidence: 85%
“…In the present study, it was not possible to analyze the temporal pattern of activity in the 3–5 Hz delta band due to edge effects surrounding the shock artefact. However, others have found that a 4 Hz oscillation develops in the mPFC during freezing behavior and that this oscillation was driven by respiration 43 45 . In line with these studies, we recently showed that respiratory frequency and delta activity frequency were highly correlated during freezing 29 .…”
Section: Discussionmentioning
confidence: 97%